2011
DOI: 10.2478/v10127-011-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Weakly ordered partial commutative group of self-adjoint linear operators densely defined on Hilbert space

Abstract: ABSTRACT. We continue in a direction of describing an algebraic structure of linear operators on infinite-dimensional complex Hilbert space H. In [Paseka, J.--Janda, J.: More on PT-symmetry in (generalized) effect algebras and partial groups, Acta Polytech. 51 (2011), 65-72] there is introduced the notion of a weakly ordered partial commutative group and showed that linear operators on H with restricted addition possess this structure. In our work, we are investigating the set of self-adjoint linear operators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…They also showed that the set of all linear operators on complex Hilbert space H with the usual sum, which is restricted to the same domain for unbounded operators (partial operation ⊕ D ), possesses this structure. In [4] we considered the structure on the important subset of self-adjoint operators, showing that it is also a wop-group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that the set of all linear operators on complex Hilbert space H with the usual sum, which is restricted to the same domain for unbounded operators (partial operation ⊕ D ), possesses this structure. In [4] we considered the structure on the important subset of self-adjoint operators, showing that it is also a wop-group.…”
Section: Introductionmentioning
confidence: 99%
“…Wop-groups have only a non-constructive associativity (the equation holds if and only if both sides are defined). It has been shown [4] that the set of all linear operators has generally stronger algebraic properties. This was a motivation for introducing the notion of a weakly ordered partial a-commutative group (woa-group) where the associative law is more constructive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation